1991
DOI: 10.1177/00220345910700030501
|View full text |Cite
|
Sign up to set email alerts
|

Acid Profile in Carious Dentin

Abstract: Organic acids in carious dentin from 69 permanent teeth were analyzed by gas chromatography. Lactate, acetate, propionate, and butyrate were detected in most samples, and limited amounts of isobutyrate, valerate, isovalerate, caproate, and isocaproate were occasionally detected. Lactate, acetate, and propionate were major acids and altogether accounted for about 90% of total acid in most samples of carious dentin. However, the proportion of these three acids varied among the samples. Some samples contained ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 17 publications
1
27
1
3
Order By: Relevance
“…Assuming, therefore, that the chromophore is organic, is it a component of the original dentine matrix or is it an exogenous molecule introduced during the carious attack? The 1989] major bacterial products associated with dentinal decay are lactic acid [Hojo et al, 1991] and proteolytic enzymes. pH is reduced in the lesion, but pH changes per se do not affect the AF signal [van der Veen and ten Bosch, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…Assuming, therefore, that the chromophore is organic, is it a component of the original dentine matrix or is it an exogenous molecule introduced during the carious attack? The 1989] major bacterial products associated with dentinal decay are lactic acid [Hojo et al, 1991] and proteolytic enzymes. pH is reduced in the lesion, but pH changes per se do not affect the AF signal [van der Veen and ten Bosch, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…The microbiotas in dentin caries consist of both acidogenic/aciduric bacteria, such as Streptococcus mutans , Lactobacillus , and Bifidobacterium species, and proteolytic/amino acid-degrading bacteria, such as Prevotella and Propionibacterium species . Reflecting this microbiological diversity, dentin caries lesions were reported to contain a variety of organic acids, and their pH was found to vary markedly [Hojo et al, 1991[Hojo et al, , 1994.…”
Section: Microbial Ecosystem Of Dentin and Root Cariesmentioning
confidence: 99%
“…In particular, Prevotella intermedia is known to exhibit protease activity at a wide range of pH (from neutral to acidic) as well as acid-producing activity [Takahashi and Schachtele, 1990]. No studies have identified a bacterial involvement in the initial degradation of dentin matrix, but the detection of bacterial metabolites in carious dentin cavities [Hojo et al, 1991[Hojo et al, , 1994 suggests that bacteria digest partly degraded dentin matrix and metabolize it into organic acids. Nevertheless, bacterial acidification is essential for the acid-induced demineralization of tooth minerals, the acid-induced denaturation of exposed and partly degraded proteins, and the acid-induced activation of host-derived proteases.…”
Section: Protein Degradation By Host-and Bacteria-derived Proteasesmentioning
confidence: 99%
“…This they achieve by acidic dissolution of hydroxyapatite, 18,19 through cracks in the tooth crown, 20 or through exposed dentinal tubules in traumatized teeth with a disconnected nerve-vessel bundle. 21 In addition, microorganisms can reach the pulp space via the apical foramen in cases of severe periodontal disease.…”
Section: Infection Of the Root Canal Spacementioning
confidence: 99%